DETERMINATION OF FACTORS ASSOCIATED WITH PLASMODIUM FALCIPARUM INFECTION AMONG HOSPITAL ATTENDEES IN SOME PARTS OF KADUNA STATE, NIGERIA - Benjamin , G. Y.; Inabo, H. I.; Doko, H. M. I.; Olayinka, B. O. (FUDMA JOURNAL OF SCIENCES, 2023)
Malaria is a significant public health problem, especially in developing countries including Nigeria. This research aimed to determine the association between some demographic factors and malaria in Kaduna State, Nigeria. Blood samples were collected from 300 participants and screened for malaria parasites using microscopy. Relevant information was obtained by administration of structured questionnaires. Occupants of compound houses had malaria prevalence of 25.0% which was higher than the 19.4% prevalence found among occupants of self-contained apartments. Higher malaria prevalence (31.8%) was found among married participants than participants who were single (16.0%) and divorced (12.5%). The association between malaria prevalence and marital status was statistically significant (p
Keywords: Malaria, Prevalence, association, Participants, Health